2009
DOI: 10.1002/elps.200800589
|View full text |Cite
|
Sign up to set email alerts
|

A proposed metabolic strategy for monitoring disease progression in Alzheimer's disease

Abstract: A specific, sensitive and essentially non-invasive assay to diagnose and monitor Alzheimer's disease (AD) would be valuable to both clinicians and medical researchers. The aim of this study was to perform a metabonomic statistical analysis on plasma fingerprints. Objectives were to investigate novel biomarkers indicative of AD, to consider the role of bile acids as AD biomarkers and to consider whether mild cognitive impairment (MCI) is a separate disease from AD. Samples were analysed by ultraperformance liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 27 publications
(22 reference statements)
2
64
0
Order By: Relevance
“…These facts agree with our experimental findings that show low levels of PUFAs-containing phospholipids and plasmalogens in AD; and high concentrations of degradation products as GPCh, Ch, and FFA, as well as SFA-containing phospholipids. Therefore, the potential of blood serum samples have been demonstrated to investigate these cerebral biochemical changes since, to date, there are only a few studies of these metabolites in this matrix [30,56,57].…”
Section: Membrane Destabilizationmentioning
confidence: 99%
“…These facts agree with our experimental findings that show low levels of PUFAs-containing phospholipids and plasmalogens in AD; and high concentrations of degradation products as GPCh, Ch, and FFA, as well as SFA-containing phospholipids. Therefore, the potential of blood serum samples have been demonstrated to investigate these cerebral biochemical changes since, to date, there are only a few studies of these metabolites in this matrix [30,56,57].…”
Section: Membrane Destabilizationmentioning
confidence: 99%
“…There are no effective treatments for AD and only very recently have biomarkers begun to show promise in predicting AD before symptoms appear (Andreasson, Vanmechelen, Shaw, Zetterberg, Vanderstichel, 2012;Mishur & Rea, 2012). Such predictive biomarkers are desperately needed as current clinical diagnosis of AD is not always accurate and is only possible well after the pathological process has begun (Graham et al, 2013;Greenberg, Grassano, Thambisetty, Lovestone, & Legido-Quigley, 2009;Hampel, Lista, & Khachaturian, 2012;Li et al, 2010). Further, genetic, epigenetic, and environmental roles in development of AD must all be considered toward a comprehensive, clinically valuable biomarker (Elias-Sonnenschein, Bertram, & Visser, 2012).…”
Section: Alzheimer's Diseasementioning
confidence: 96%
“…Other plasma lipids classes reported to have close relationships with AD included bile acids (Greenberg et al, 2009), LysoPCs and (Trushina et al, 2013b) AD(n = 3) FTD(n = 4) LBD(n = 3) CN(n = 9) Serum CE-MS ↑b-alanine, creatinine, hydroxyproline, glutamine, isocitrate, cytidine (Tsuruoka et al, 2013) AD(n = 12) CN(n = 5) Whole brain MRS ↓N-acetyl-aspartate, g-aminobutyric acid; ↑ glutamate (Klunk et al, 1992) AD ( Changes in levels of uracil, xanthine, uridine, tyrosyl-serine, methylsalsolinol, nonanoylglycine, dopamine-quinone, caproic acid, vanylglycol, histidine, pipecolic acid, hydroxyphophinylpiruvate, creatinine, taurine, C16-sphingosine-1-phosphate, tryptophan, 5 0 -methylthioadenosine (Ibanez et al, 2013) phytosphingosine (sphingolipid precursors) (Li et al, 2010b), among others (Mapstone et al, 2014). Utilizing in-vial dual extraction protocol Godzien et al, 2013), abnormal levels of long chain cholesteryl esters/triglycerides (Proitsi et al, 2015;Proitsi et al, 2017) and omega-3 containing PC molecules (Whiley et al, 2014;Kim et al, 2016) have been shown in two separate study cohorts.…”
Section: Bloodmentioning
confidence: 99%